Training On The Use Of Young Areca Nut Slicing Machine To Increase The Work Capacity Of Areca Nut Slicing - Allen, Rio Valery; Ernita, Yuni; Novita, Sri Aulia (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
The post-harvest processing of areca nut (Areca catechu L.) in Fifty Thousand Kota District, which has a plantation area of 1,254 ha with a production of 196.12 tons/year, is often done manually, especially at the stage of slicing young areca nuts into thin slices. The manual method using knives or cutters is time-consuming (8 minutes/kg) and carries a high risk of cuts. However, sliced areca nuts have a higher selling price and low water content (0.9%), which increases farmers' sales by up to 45% compared to whole nuts. Therefore, this community service activity (PkM) aims to overcome these problems through training and demonstrations on the use of young areca nut slicing machines to 15 participants from farmer groups at the FRD Pinang Raya SME, Mungo, Limapuluhkota Regency. The methods used include coordination, needs assessment, machine testing, and participatory practical training. The results of the activity showed that this training successfully improved the participants' understanding and skills in operating and maintaining the machine. This technology transfer has been proven to increase time efficiency and productivity, producing faster and more uniform pineapple slices compared to the manual method. Overall, this PkM has succeeded in empowering the community through practical solutions to post-harvest processing problems, contributing to increased processing efficiency and the potential for economic improvement for partners.